A short reflection addressed to the analysts about the relationship between mass spectrometry and sample preparation - Andreas S. L. Mendez; Matthew S. Halquist (Drug Analytical Research)
Mass spectrometry is one of the most advanced technology applied to qualitative and quantitative analysis. The complexity related to this technique is not the only critical aspect to be considered in the routine of analysis. Actually the quality of analytical results is dependent on previous steps involved to the sample preparation, where well established protocols, conditions, solvents, dilutions, i.e. are crucial to have excellence in the analytical performance. All analysts involved must be qualified and recognize the importance of an integrative view about the sample, from different sources, complex or not, and the protocols to be applied sequentially in order to get prepared for a running through mass spectrometry or hyphenated system (LC-MS). In this work, through a simple and short reflection, the analysts are encouraged to reflect deeply about the importance of these two topics – mass spectrometry and sample preparation – to get excellence during the analytical routine.